PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN WORDWALL TERHADAP HASIL BELAJAR MATA PELAJARAN BAHASA INDONESIA UPTD SD NEGERI 77 PAREPARE - Usman; Sultan, Muhammad Asrul; Nurhaliza A.L., Andi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study objective to determine the effect of using Wordwall learning media on student achievement and reading skills of students of Bahasa Indonesia subjects UPTD SD Negeri 77 Parepare. This research uses quantitative methods with experimental research in the form of one group pretest-posttest. The population of this study were all students at UPTD SD Negeri 77 Parepare. with a sample 20 class v students using random sampling technique. Data collection was carries out by giving initial tests and final tests to measure student achievement before and after the use of Wordwall student achievement and reading skills of students in Bahasa Indonesia subject. The data analysis technique used was paired sample t-test to test average difference in learning outcomes before and after treatment. This finding indicates a significant difference between student learning media on improving the student achievement before and after using Wordwall learning media. Thus, it can be concluded that there is a positive and significant effect of using Wordwall learning media on improving the outcomes of reading skills in Bahasa Indonesia subjects of grade V students of UPTD SD Negeri 77 Parepare.